International Taxation and the Extractive Industries. (International Monetary Fund, 2016)
The taxation of extractive industries exploiting oil, gas, or minerals is usually treated as a sovereign, national policy and administration issue.This book offers a uniquely comprehensive overview of the theory and practice involved in designing policies on the international aspects of fiscal regimes for these industries, with a particular focus on developing and emerging economies. International Taxation and the Extractive Industries addresses key topics that are not frequently covered in the literature, such as the geo-political implications of cross-border pipelines and the legal implications of mining contracts and regional financial obligations. The contributors, all of whom are leading researchers with experience of working with governments and companies on these issues, present an authoritative collection of chapters. The volume reviews international tax rules, covering both developments in the G20-OECD project on 'Base Erosion and Profit Shifting' and more radical proposals, identifying core challenges in the extractives sector. This book should become a core resource for both scholars and practitioners. It will also appeal to those interested in international tax issues more widely and those who study environmental economics, macroeconomics and development economics.